Impact of glucose metabolism on myocardial fibrosis and inflammation in hypertrophic cardiomyopathy: a cardiac MR study - Xin Peng; Xin Peng; Huaibi Huo; Zhengkai Zhao; Qiuyi Cai; Jiangyu Tian; Dandan Yang; Yao Song; Yuheng Huang; Zhuoan Li; Jin Gao (Frontiers in Endocrinology)
Diabetes mellitus increases the risk of adverse cardiovascular outcomes in hypertrophic cardiomyopathy (HCM) patients. This retrospective study aimed to evaluate myocardial microstructural alterations, particularly fibrosis and subclinical inflammation, in HCM patients across glycemic statuses using multiparametric cardiac magnetic resonance (CMR). Additionally, it explored the correlation between myocardial fibrosis and hemoglobin A1c (HbA1c) levels. 108 HCM patients were stratified by HbA1c levels into non-diabetic (n=38), prediabetic (n=40), and diabetic (n=30) subgroups, along with 30 healthy controls. All participants underwent 3.0-T CMR examination. Compared to non-diabetic HCM patients, prediabetic and diabetic HCM patients exhibited progressively higher mean T1 values and extracellular volume fractions (ECV) (p < 0.001). Similar trends were observed in hypertrophic myocardial regions, with diabetes patients showing pronounced fibrosis. Mean ECV exhibited a strong positive correlation with HbA1c levels (r = 0.634, p < 0.001). In the fully adjusted model, both T1 values and ECV demonstrated significant associations with HbA1c levels. Subclinical myocardial inflammation, as evidenced by elevated T1 and T2 values, was observed in prediabetic and diabetic patients but not in non-diabetic patients. Progression of myocardial fibrosis in HCM is linked to elevated HbA1c, especially in hypertrophied regions, even in prediabetic individuals. Subclinical myocardial inflammation was observed in HCM with glucose metabolism abnormalities. These findings underscore the importance of early glycemic control and the integration of CMR-based tissue characterization into HCM management strategies.